POLA REPRESENTASI PIHAK ISRAEL DALAM ENSIKLOPEDIA BRITANNICA - NFN Sunarsih (Kantor Bahasa Sulawesi Tenggara, 2017)
The existence of Israel generates many discourses in so many media and in various points of view. One of the media writing about Israel is Britannica, an internationally high-reputed encyclopedia. Since the intellectual competence is embedded to Britannica, every article published in it may be considered as academically correct. This paper is aimed at analyzing the patterns of Israeli representation in Britannica by applying corpus-based critical discourse analysis (a method combining critical discourse analysis and linguistic corpus). The patterns are analyzed from the concordance of a key word “Israeli(s)” and the collocation around the key word. The results of the study showed that Britannica represents Israel as a powerful military force, as a country that runs democracy, as a country with complete governmental institutions, as one of the main actors of regional conflict, and as the side which affords the conflict end. The patterns found tend to be paradoxical each other because the bad and good side of Israel are represented interwovenly. It implies that Britannica does not construct Israel as entirely black or white.